Readability, Content, Quality, and Accuracy Assessment of Internet-based Patient Education Materials Relating to Labor Analgesia. Issue 2 (June 2020) - Murphy, J.; Vaughn, J.; Gelber, K.; Geller, K.; Zakowski, M.
Abstract : ( Int J Obstet Anesth . 2019;39:82–87) It has been reported that >90% of pregnant women in the United States and Western Europe conduct internet searches for health information related to pregnancy. However, 66% of these women believed that information they obtained from a Web site may have been inaccurate or misleading; this potentially wrong content caused them worry about their pregnancy and/or delivery. With pregnancy information widely available online, it is important for health care professionals to monitor the quality and accuracy of the information their patients are receiving from internet sources. In this study, the investigators compared patient education materials (PEMs) provided by national and international medical societies to PEMs found via a Google search, assessing the readability, content, quality, and accuracy of the information.